Rancang Bangun Sistem Informasi Penerimaan Karyawan Pada PT. Doo Seung Global Berbasis Web - Hardandrito, Awan Gumilang; Suhardoyo, Suhardoyo (RIGGS: Journal of Artificial Intelligence and Digital Business, 2025)
The development of information technology in the business world is getting tighter. With the support of quality human resources, it will support company management to be able to survive in its activities. The key to success in getting quality human resources lies in the employee recruitment stage. So it is necessary to have a better employee recruitment management system. Like PT. Doo Seung Global as a company engaged in the manufacture of knitted materials such as sweaters, cardigans, scarves and vests, the employee recruitment process still uses a manual system. This causes problems, including damaged or lost applicant data and takes a lot of time in the hiring process, and the availability of updated data is not guaranteed. To provide a solution, the authors designed a web-based employee recruitment information system, the authors used the waterfall model software development method to design an information system and used Unified Modeling Language (UML) diagrams, a website-based Employee Recruitment Information System at PT. Doo Seung Global can help the employee recruitment process become faster, precise and accurate in order to get employee candidates who meet the criteria